First record of Tettigometridae (Hemiptera: Fulgoromorpha) from Pakistan: description of a new species including barcode identification - Sohail, Kamran; Huang, Weijian; Usman, Muhammad; Zhang, Yalin (Zootaxa, 2020)
Tettigometra ziaratensis sp. nov. is described from Ziarat, Baluchistan, Pakistan; it is the first record of the genus Tettigometra Latreille, 1804 and the family Tettigometridae from this country. Sequence data for the barcoding region of the mitochondrial gene COI for this new species was obtained and deposited in GenBank.